Some sum to sum

n=1xn2x2=12(1xπcot(πx))\large \sum _{n=1}^{\infty}\dfrac{x}{n^2-x^2}=\frac{1}{2}\left(\dfrac{1}{x}-{\pi \cot \left(\pi x\right)}\right)

Prove that the equation above holds true for x0x\ne 0 .

#Calculus

Note by Julian Poon
5 years, 1 month ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Consider the infinite product of sinxx\dfrac{\sin x}{x},

sinxx=n=1(1x2(nπ)2) \displaystyle \dfrac{\sin x}{x} = \prod_{n=1}^{\infty} \left( 1 - \dfrac{x^2}{(n\pi)^{2}}\right)

Substitute xπxx \mapsto \pi x

    sinπxπx=n=1(1x2n2)\implies \displaystyle \dfrac{\sin \pi x}{\pi x} = \prod_{n=1}^{\infty} \left( 1 - \dfrac{x^2}{n^{2}}\right)

Taking logarithm and differentiating w.r.t. xx on both sides, we get,

n=12xn2x2=πxcot(πx)x1x \displaystyle - \sum_{n=1}^{\infty} \dfrac{2x}{n^2 -x^2} = \dfrac{\pi x \cot (\pi x)}{x} - \dfrac{1}{x}

    n=1xn2x2=12(1xπxcot(πx)x)\displaystyle \implies \sum_{n=1}^{\infty} \dfrac{x}{n^2 -x^2} = \boxed{\dfrac{1}{2} \left( \dfrac{1}{x} - \dfrac{\pi x \cot (\pi x)}{x} \right)}

Ishan Singh - 5 years, 1 month ago

The function F(z)  =  1z+n=12zz2n2  =  nZ1zn F(z) \; = \; \frac{1}{z} + \sum_{n=1}^\infty \frac{2z}{z^2-n^2} \; = \; \sum_{n \in \mathbb{Z}} \frac{1}{z-n} is analytic on C\Z\mathbb{C} \backslash \mathbb{Z}, periodic of period 11, and has simple poles with residue 11 at each integer. The same is true of the function G(z)  =  πcotπz G(z) \; = \; \pi\cot \pi z Thus F(z)G(z)F(z) - G(z) is an entire function on C\mathbb{C}. It is not difficult to show that FGF-G is a bounded function - find a bound for Rez12|\mathrm{Re} z| \le \tfrac12 and Imz1|\mathrm{Im} z| \ge 1 by getting your hands dirty with the definition of each function, find a bound for Rez12|\mathrm{Re} z| \le \tfrac12 and Imz1|\mathrm{Im} z| \le 1 by continuity, and use periodicity to deduce boundedness everywhere.

Thus it follows that FGF-G is constant. Test the value at one point, such as z=12z=\tfrac12, to confirm that FF and GG are equal.

Mark Hennings - 5 years ago
×

Problem Loading...

Note Loading...

Set Loading...